A new delivery system for 5-fluorouracil using prodrug and converting enzyme. Issue 5 (1st May 2002) - Akimoto, M; Miyahara, T; Arai, J; Akimoto, A; Hamada, H; Yoshida, Y; Yoshimura, N
Abstract : Aims: To evaluate a new delivery system of 5-fluorouracil (5-FU) using 5-fluorocytosine (5-FC) as a prodrug and cytosine deaminase induced in vitro and in vivo. Methods: Fibroblastic cells from rabbit Tenon's capsule were cultured. The cells were exposed to 5-FU and 5-FC with or without cytosine deaminase induced by recombinant adenovirus. In the in vitro study, cell proliferation and DNA synthesis were assessed by MTS, BrdU assay. The effect of 5-FC removal after the treatment of 5-FC and cytosine deaminase induction was also assayed. In the in vivo study cells with or without cytosine deaminase induction were transplanted into the subconjunctival space of mice, followed by eye drops of 1000 μg/ml of 5-FC three times a day. The mice were sacrificed at days 1, 5, and 10, then the cells transplanted were evaluated. Results: Cell proliferation was inhibited by exposure to 5-FU in a dose dependent manner; however, up to 1000 μg/ml of 5-FC did not affect cell proliferation. Cell proliferation was inhibited by exposure to 5-FC in a time dependent manner with induction of cytosine deaminase following infection of recombinant adenovirus. When 5-FC was removed 3 or 6 days after the treatment, the cells grew again. The effect was reproduced in the in vivo model of subconjunctival cellular proliferation although 5-FC was administrated as eye drops. There were no cases with corneal erosion. Conclusion: Cell proliferation was inhibited by co-exposure of 5-FC and cytosine deaminase. This new delivery system may merit controlled delivery of 5-FU after filtering surgery.